Fungi that cause superficial mycoses : - Tan, C. Shu-hui (International Association, 1994)
The content of this book was primarily to serve as a guide for a short course for dermatologissts.Drring this book the true dermatophytes belonging to the genera trichophyton, mycrosporum and epidermophyton are treated.